Grip pressure distributions and associated variability in golf: a two-club comparison - Langlais, S. M.; Broker, J. P. (Sports Biomechanics, 2014)
Teaching and playing professionals offer multiple theories concerning the manner in which forces should be applied to the handle of the club during the golf swing. This study extends recent research concerning grip pressures and forces in golf, with the purpose of exploring the similarities and differences between force profiles for a 7-iron and driver swung by proficient golfers. A secondary purpose was to further analyze the way that golfers use grip forces to manipulate the club. Grip forces were measured on eight low handicap golfers (USGA indexes 0 to 7) swinging their own 7-irons and drivers. In total, lead-hand and trail-hand grip forces were isolated as well as anatomically specific forces within the hands. Force profile variability across multiple swings for each golfer and between golfers characterized consistencies and important differences. Correlations between 7-iron and driver force profiles characterized force `signatures.` The data highlight large fluctuations in grip forces during the swing. Marked differences between participants were observed, involving force magnitudes and phasing. Dominant forces arose primarily from the lead hand, specifically the last three fingers. Force profiles were highly repeatable across swings for a golfer (standard deviations < 7% of total force) and force profile correlations between 7-iron and driver for a golfer were remarkably high (r2 = 0.86). Notably, within swing force variability was greatest during club acceleration, but dramatically decreased at impact.